-2(2x+3)+8x=6(x-1)+3x

Simple and best practice solution for -2(2x+3)+8x=6(x-1)+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(2x+3)+8x=6(x-1)+3x equation:


Simplifying
-2(2x + 3) + 8x = 6(x + -1) + 3x

Reorder the terms:
-2(3 + 2x) + 8x = 6(x + -1) + 3x
(3 * -2 + 2x * -2) + 8x = 6(x + -1) + 3x
(-6 + -4x) + 8x = 6(x + -1) + 3x

Combine like terms: -4x + 8x = 4x
-6 + 4x = 6(x + -1) + 3x

Reorder the terms:
-6 + 4x = 6(-1 + x) + 3x
-6 + 4x = (-1 * 6 + x * 6) + 3x
-6 + 4x = (-6 + 6x) + 3x

Combine like terms: 6x + 3x = 9x
-6 + 4x = -6 + 9x

Add '6' to each side of the equation.
-6 + 6 + 4x = -6 + 6 + 9x

Combine like terms: -6 + 6 = 0
0 + 4x = -6 + 6 + 9x
4x = -6 + 6 + 9x

Combine like terms: -6 + 6 = 0
4x = 0 + 9x
4x = 9x

Solving
4x = 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
4x + -9x = 9x + -9x

Combine like terms: 4x + -9x = -5x
-5x = 9x + -9x

Combine like terms: 9x + -9x = 0
-5x = 0

Divide each side by '-5'.
x = 0

Simplifying
x = 0

See similar equations:

| 8-6x=3-7x | | 10=2h | | 28.50+8.75w=104.75+6.50w | | 9Y-81x=108 | | 6q+3q-q=24findq | | 90x+x=90 | | 8x+4y=10y | | 6x-2=-4c+8x | | 180x+x=180 | | 2(2-x)=8-2(2-x) | | f(x)=(15x) | | y+16=20 | | 90x+x=180 | | 10-.25x=.5+4 | | 4(v+5)+8v=32 | | x^2-10x-27=0 | | x-76y=0 | | 12x^2+6x+82=0 | | 4x^2-5sinx=0 | | -5n-3n+2=34 | | 18x-6=-10 | | 4x^2-5sinx= | | (6+u)(3u+4)=0 | | (27x)27=21(21+2x+8) | | 2(2-x)=8-2(-x) | | ln(6)+ln(x)=4 | | 2x+3(2+5)=X | | 4(3x^2+2x)-12x^2=2(8x+6) | | 4x+3(x-6)=-11 | | -6-(21-6X)=-51+2X | | 4x-9y+6x+3y-2x=0 | | 3(2x-6)-(2x+1)=9 |

Equations solver categories